فعالية استخدام كتاب التصريف لتنمية مهارة القراءة لطلاب الفصل الثاني الابتدائي - Segaf Baharun; Abdul Kholiq (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2024)
The researcher noticed, in the process of teaching the Arabic language, especially in the second grade of primary school at Jannatul Naeem Falankaraya Institute, that teaching the Arabic language, especially the reading skill, is surrounded by many problems, so that the desired goal of education has not been fully achieved. The morphology book is one of the means that will be used to develop the reading skill, because the researcher finds that in the second grade of primary school, the students have learned grammar and the book used there is the text of Ajrumiyyah, but unfortunately the students have not studied morphology. Based on the above, the researcher wanted to solve this problem by conducting scientific research using the morphology book and the effectiveness of its use in teaching reading skills to students in this school. The approach used by the researcher is the quantitative approach. The result of using the morphology book in the Arabic language in an experimental group is effective because the score reached a score of 4.39 for the experimental group, this number is greater than the score of 4.39 for the The table is at the significance level of 5% and 1%. The t-score is 2.08 for the control group, which is smaller than the t-score in the table at the significance level of 5% and 1%..